2010
DOI: 10.1007/978-3-642-11598-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Low Voltage Thermo-mechanically Driven Monolithic Microgripper with Piezoresistive Feedback

Abstract: Pick-and-place of micro/nano sized objects means handling of very tiny and very different in properties objects having specific behavior. Besides formal requirements of assembly processes, the tools for controllable manipulation with these objects should not affect the examined micro/nano environment, i.e. should be "small and passive" in any sense. Despite of the recent progress, most available micro-grippers are still suffering of high voltage power supply required, short lifetime, low detection sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The forward movement of the shaft opens the gripper by rotation of the arms. Several studies demonstrated structures fabricated from nickel [69], silicon [73], polymer [74], and also a normally-open microgripper structure [75]. Other examples can use complex compliant structures to operate the gripper arms.…”
Section: V-shape Chevron Actuatorsmentioning
confidence: 99%
“…The forward movement of the shaft opens the gripper by rotation of the arms. Several studies demonstrated structures fabricated from nickel [69], silicon [73], polymer [74], and also a normally-open microgripper structure [75]. Other examples can use complex compliant structures to operate the gripper arms.…”
Section: V-shape Chevron Actuatorsmentioning
confidence: 99%
“…A few of the most frequently used principles are, for example, electro thermal (Volland et al 2007;Stavrov 2010, Colinjivadi et al 2008Solano and Wood 2007;Zeman et al 2006;Voicu et al 2007) electrostatic (Beyeler et al 2007;Wierzbicki et al 2006), piezoelectric (Nah and Zhong 2007;Perez et al 2006), electromagnetic (Kim et al 2005) or are based on the shape memory effect (Zhong and Chan 2007). All these techniques have their specific advantages and disadvantages, e.g.…”
Section: Introductionmentioning
confidence: 97%